Health in focus: HPV - Neves Guimarães de Carvalho, Rozana; de Fatima Peixoto Casimiro, Maria; Rodrigues Demberg, Rafaela; Silva Motta, Larissa; Xavier de Paula Veraldo, Julia; Pereira dos Santos, Isabelle; de Oliveira Domingos da Silva, Camila; Leonel de Oliveira, Tiago; Moreira Poeys, Jéssica; Luiz Lima da Silva, Jorge (Seven Editora, 2023)
The present study is concerned with discussing the infection caused by the human papillomavirus (HPV), going through themes about the means of transmission, detection, most common signs and symptoms, strategies for promotion and prevention, and treatment in Primary Care. In addition, it is concerned with exposing the interventions of nursing professionals in the Primary Care scenario. The bibliographic survey was carried out through scientific articles found in the electronic databases Scielo and Google Scholar. Additionally, magazines with the theme of interest. We opted, preferably, for works prepared in the period from 2018 to 2023. The lack of information has been favoring excessive propagation and putting the health of the population at risk. Thus, in observing a deficiency in the knowledge of this virus, it is expected to amplify knowledge, considering that it represents a considerable public health problem.DOI: https://doi.org/10.56238/devopinterscie-113